Cyclooxygenase-2 Mediated Regulation of E-Cadherin Occurs in Conventional But Not Early-Onset Gastric Cancer Cell Lines - Sitarz, R. (Cell Oncol, 2009)
Background: COX-2 and E-cadherin, involved in invasion and metastasis, are molecules critical for gastric carcinogenesis. A relationship between them is documented in non-small cell lung and prostate cancer. We present novel evidence of a relationship between COX-2 and E-cadherin expression in gastric cancer. Methods: Using qPCR and Western blots analysis on celecoxib and PGE2 treated and untreated gastric cancer cell lines derived from tumours of the intestinal type (MKN45, MKN28, AGS3, MKN7) and immunohistochemistry of 178 gastric cancers on tissue microarrays (TMA), we examined the COX-2/E-cadherin relationship. Results: Down-regulation of COX-2 by celecoxib led to up-regulation of E-cadherin mRNA and protein levels in conventional gastric cancer cell lines, whereas expression was down regulated in the early-onset gastric cancer (EOGC) cell line. Immunohistochemistry on TMAs of 178 gastric cancers showed no correlation between COX-2 and E-cadherin expression in the conventional or early gastric cancer groups. Conclusions: The results suggest that COX-2 has an impact on transcriptional regulation of E-cadherin in gastric cancer and our findings further highlight the intriguing nature of EOGCs which appear to have a molecular phenotype distinct from conventional gastric cancer. In addition, our findings also suggest that reduction of COX-2 using nonsteroidal anti-inflammatory drugs in gastric cancer chemoprevention may only be relevant for older patients.